2003
DOI: 10.1128/aac.47.12.3764-3767.2003
|View full text |Cite
|
Sign up to set email alerts
|

Increased Killing of Staphylococci and Streptococciby Daptomycin Compared with Cefazolin and Vancomycin in an InVitro Peritoneal DialysateModel

Abstract: Peritoneal dialysate fluid (PDF) is a bacteriostatic medium that compromises the antibacterial activity of cell wall-active agents. By use of an in vitro static model, methicillin-resistant Staphylococcus aureus (MRSA), methicillin-susceptible S. aureus (MSSA), methicillin-susceptible Staphylococcus epidermidis (MSSE), and Streptococcus sanguis were exposed to daptomycin at concentrations of 10, 30, and 100 mg/liter, cefazolin at 125 mg/liter, and vancomycin at 25 mg/liter in cation-adjusted Mueller-Hinton Bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 20 publications
3
46
0
Order By: Relevance
“…In vitro studies evaluating the activity of DAP against various streptococci, including VGS, have shown significant kill without development of resistance. There is only a single report for an in vitro peritoneal dialysate model where DAP at 10 mg/liter against Streptococcus sanguis (S. sanguinis) displayed more static activity with only a 2-log 10 CFU reduction compared to Ͼ3 log 10 CFU reduction with cefazolin and VAN (42). In addition to reduced activity of DAP, regrowth occurred in the model by 24 h with the authors attributing this to the possibility of inadequate calcium supplementation within the growth media despite noting that the calcium concentration was greater than 50 mg/liter.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies evaluating the activity of DAP against various streptococci, including VGS, have shown significant kill without development of resistance. There is only a single report for an in vitro peritoneal dialysate model where DAP at 10 mg/liter against Streptococcus sanguis (S. sanguinis) displayed more static activity with only a 2-log 10 CFU reduction compared to Ͼ3 log 10 CFU reduction with cefazolin and VAN (42). In addition to reduced activity of DAP, regrowth occurred in the model by 24 h with the authors attributing this to the possibility of inadequate calcium supplementation within the growth media despite noting that the calcium concentration was greater than 50 mg/liter.…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin is a cyclic lipopeptide antibacterial agent that exhibits rapid, concentration-dependent in vitro bactericidal activity against clinically significant strains of gram-positive pathogens, including streptococci, methicillin-resistant S. aureus, and vancomycin-resistant enterococci (5,13,18,31). In the present study, the observed bactericidal activity against stationary-phase S. aureus ATCC 29213 is remarkable since most other bactericidal agents interfere with cell division or on May 10, 2018 by guest http://aac.asm.org/ processes necessary for cell division and typically have little activity against nondividing cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin is a lipopeptide antibiotic that displays rapid bactericidal activity in vitro against gram-positive pathogens, including streptococci, methicillin-resistant S. aureus, and vancomycin-resistant enterococci (5,13,18,31). Daptomycin works by disrupting membrane function and causing leakage of essential potassium ions, ultimately leading to loss of membrane potential and cell death (26).…”
mentioning
confidence: 99%
“…However, the relatively poor pharmacodynamic effects of both these drugs compared to those of the fluoroquinolones might have resulted in a lower eradication efficacy due to the slower bactericidal action of vancomycin and the bacteriostatic effect of linezolid (6,12). The superior pharmacokinetic advantages of vancomycin and linezolid are reflected by the lower protective doses that we found in the mouse protection studies (survival with linezolid treatment; data not shown).…”
Section: Discussionmentioning
confidence: 81%